Protecting Youth and Volunteers by Planning Ahead, Reducing Risk - Keith G. Diem (EDIS)
The UF/IFAS Extension 4-H Youth Development Program is committed to the safety and well-being of its youth as well as the volunteers who help deliver 4-H programs under the supervision of 4-H faculty and staff. All things in life involve some sort of risk. This is especially true when working with youth, but there are many ways that volunteers can minimize this risk and lead safe 4-H activities. Proper planning and common sense certainly go a long way. Although not to be considered legal advice, here are some facts and issues to know and keep in mind while serving as a 4-H volunteer. This 3-page fact sheet was written by Keith G. Diem, and published by the UF Department of 4-H Youth Development, July 2014.